Tinjauan Keadilan terhadap Advokasi Masyarakat dalam program Desa Inklusif Disabilitas di Bah Sulung, Kabupaten Simalungun - Sihombing, Helpin; Tampake, Tony; Ludji, Irene (Jurusan Pendidikan Luar Biasa, 2022)
People with disabilities still do not receive optimal services overall. People with disabilities need to receive space for justice and prosperity from their families and society. This research aims to analyze and explore the justice received by people with disabilities in Bah Sulung Village through the disability inclusive village program. The disability inclusive village program is an effort by the church and community by establishing an RBM (Community Based Rehabilitation) Post in Bah Sulung Village. Data analysis was carried out descriptively qualitatively. In collecting data, the author conducted observations and interviews as well as literature studies in Bah Sulung Village to investigate the fulfillment of rights and equality obtained by people with disabilities. The informants consisted of RBM post administrators, RBM cadres, families of people with disabilities and several communities in Bah Sulung Village, Simalungun. The research results show that people with disabilities and their families gain acceptance and equality through the empowerment of RBM posts. The author uses John Rawls's perspective on justice theory as a basis for analyzing justice issues for people with disabilities in fulfilling equality and rights.